Simulation of quantum shortcuts to adiabaticity by classical oscillators - Liu, Yang; Zhang, Y. N.; Liu, H. D.; Sun, H. Y. (Frontiers in Physics, 2023)
It is known that the dynamics and geometric phase of a quantum system can be simulated by classical coupled oscillators using the quantum−classical mapping method without loss of physics. In this work, we show that this method can also be used to simulate the schemes of quantum shortcuts to adiabaticity, which can quickly achieve the adiabatic effect through a non-adiabatic process. By mapping quantum systems by classical oscillators, two schemes, Berry’s “transitionless quantum driving” and the Lewis−Riesenfeld invariant method, are simulated by a corresponding transitionless classical driving method, which keeps adiabatic phase trajectories and acquires Hannay’s angle and the classical Lewis−Riesenfeld invariant method by manipulating the configurations of classical coupled oscillators. The classical shortcuts to adiabaticity for the two coupled classical oscillators, which is the classical version of a spin-1/2 in a magnetic field, is employed to illustrate our results and compared with quantum shortcuts-to-adiabaticity methods.